Brill's companion to the study of Greek comedy - Dobrov, Gregory W., 1957- (Brill's Companions to Classical Studies., 2010)
The present volume sets forth the main resources for the advancing student of Ancient Greek Comedy. An international roster of specialists contributes chapters organized into three sections: \'Contexts\': the intellectual, physical and socio-historical setting of Athenian Comedy; \'History\': the literary history of the Old, Middle and New periods; and \'Elements\': the text, language and formal components of the genre (including a comprehensive bibliography). This Companion is designed as a resource for understanding and interpreting the classics of Athenian Comedy from its inception through Menander. It will also be useful for navigating the principal corpora of texts, fragments and scholia that have been revised and augmented in recent years.This unique volume occupies the middle ground between short surveys and highly specialized scholarship. Contributors include: W. Geoffrey Arnott, Angus Bowie, Eric Csapo, Gregory W. Dobrov, J. Richard Green, Stanley Ireland, Heinz-Günther Nesselrath, S. Douglas Olson, Alan H. Sommerstein, Ian Storey, Ralph M. Rosen, Andreas Willi, Bernhard Zimmermann.